Projeto de uma bancada didática para ensino de geração de energia solar fotovoltaica - VIEIRA, Gilberson Lander da Silva (Universidade Federal do Oeste do Pará, 2024)
Solar energy is a source of energy from the sun, which is highly important to mankind, a vital source for the maintenance of all life on Earth. It is the basis of all other sources of energy that exist. Photovoltaic solar energy is one of the ways of using this energy source, considered clean and renewable, transforms sunlight into electricity through the photovoltaic effect, it seeks to replace polluting sources of energy from the world energy matrix, which harm the environment and the atmosphere. Currently it is verified that the academic formation in the universities is basically based on theoretical education, but it is important to emphasize that the students need a practical application of some disciplines that they will use in their professional life or in research projects. In this context the present work presents the development and construction of a didactic bench for the teaching of photovoltaic solar energy generation. The didactic bench has movements that simulate the solar declination angles, the hour angle and the angular variation of the solar panel. Important parameters of the energy generation will be evaluated as, electric voltage, electric current, irradiation and temperature, as a function of the movement of the Sun in relation to the angular movements presented on the solar panel.